2013
DOI: 10.1200/jco.2013.49.3981
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to CONSORT Adverse Event Reporting Guidelines in Randomized Clinical Trials Evaluating Systemic Cancer Therapy: A Systematic Review

Abstract: Our findings show that some methodologic aspects of AE collection and analysis were poorly reported. Given the importance of AEs in evaluating new treatments, authors should be encouraged to adhere to the 2004 CONSORT guidelines regarding AE reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 31 publications
2
75
1
1
Order By: Relevance
“…This approach is broadly applicable to clinical trial publications because no single journal, therapeutic area, author group, or sponsor performs consistently better than each other in this regard. [3][4][5][6][7][8][9] Thirdly, authors should discuss how the individual trial results relate to the larger body of clinical evidence in order to help practitioners and future investigators better understand the evolving adverse event profile of a new intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is broadly applicable to clinical trial publications because no single journal, therapeutic area, author group, or sponsor performs consistently better than each other in this regard. [3][4][5][6][7][8][9] Thirdly, authors should discuss how the individual trial results relate to the larger body of clinical evidence in order to help practitioners and future investigators better understand the evolving adverse event profile of a new intervention.…”
Section: Discussionmentioning
confidence: 99%
“…2 While adverse event reporting subsequently improved, the overall communication of adverse event data continues to be suboptimal. [3][4][5][6][7][8][9] For example, a 2013 review of 325 randomized clinical trials published between 2007 and 2011 described inadequate or uninformative reporting of adverse event collection and analysis methodology, 9 suggesting poor adherence to the CONSORT Harms Extension in that sizeable trial sample. Moreover, existing guidance in the CONSORT Harms Extension, while rigorous and broadly applicable across disease areas, can lack the level of specificity regarding clinically meaningful adverse events necessary for practical clinical application.…”
mentioning
confidence: 99%
“…Severity Skew. The type of AEs recorded in Phase II/III trials specifically have been reported to skew toward a focus on only high-grade (grade 3 or 4) toxicities, pool toxicities of varying severity, include both quantitative and qualitative evaluations, and/or misgrade toxicities [125,126]. Thus, it is possible that a significant pool of AE data may be systematically excluded from these evaluations.…”
Section: Synthesis Of Results Of Literature Evaluationsmentioning
confidence: 99%
“…Country of trial origin, sample size and whether the study was a LTE of a previously published trial or not were independent predictors significantly associated with higher THRS. Reviews evaluating quality of harms reporting in oncology9 and analgesic10 RCTs also reported better reporting of AEs in trials funded by industry. This may be explained by tighter control by regulatory agencies for industry-funded trials, better and thorough data collection capabilities and soliciting services of professional medical writers in manuscript writing 9…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that authors might have collected this information but could not report it due to restrictions on manuscript length. Manuscript length can be one of the reasons for not adequately reporting AEs 9. The option of ‘online only’ supplement is offered by almost all journals now which could be used to report additional harms-related data.…”
Section: Discussionmentioning
confidence: 99%